Molecular docking and dynamic simulation of phytochemical components from Clitoria ternatea against different hormone-dependent Cancer Cell Lines (Indian Journal of Chemistry (IJC), 2025)
Creating novel non-toxic drug candidates targeting breast cancer cells with no effects on normal cells is on the top of research objectives. Blue Clitoria ternatea (C. ternatea) flowers macerated in ethanol and evaporated using precision economy incubator at  to isolate the major phytochemical compounds. GC-MS technique was used to identify the chemical structure of isolated components. Biomolecular and pharmacokinetics analytical tools were used to measure the binding affinity, stability, and solubility of selected compounds targeting caspase-3 modeling. Normal HSFs, and different breast cancer cell lines were grown for 24 and 48 hours to evaluate cytotoxic activities of extracted C. ternatea compounds. Computational analysis of compound CID-22212496 (Cholesta-8,24-dien-3-ol) showed poor solubility, stable binding affinity (-7.6 kcal/mol), and strong interactions across several key residues such as LYS-105, ASP-135, and ASN-141. Antiproliferative experiments showed no toxic activities of extracted compounds on cell growth of normal HSFs cells with value of 923.9±5.33 µg/ml. In contrast, significant cell growth reduction was observed particularly in breast MDA-MB-231 cancer cells withvalues of 363.06±6.94 µg/ml and 209.4±4.06 µg/ml following 24 and 48 hours of treatment, respectively. We suggest that Cholesta-8,24-dien-3-ol compound can be promising anticancer candidate against estrogen-sensitive cancer cells by intermitting estrogen biosynthesis through activation caspase-3.